MAJELIS TAKLIM SEBAGAI MEDIA PEMBERDAYAAN PEREMPUAN DI PERUMAHAN VILLA KARAWANGI - Nur Afifah, Hana; Iwan Hermawan; Nia Karnia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the role of the taklim council as a means of women's empowerment in the Villa Karawangi Housing area. The taklim council is not only used as a medium for religious learning, but also serves as a space to improve women's social, economic, and spiritual abilities. This study uses a qualitative approach with a field study method. Data collection was carried out through observation, interviews, and documentation involving the chairman of the taklim council, members, and activity managers. The results of the study show that the taklim council in Villa Karawangi Housing makes a considerable contribution to women's empowerment efforts, especially in increasing religious understanding, strengthening social relations, and encouraging independence through various productive economic activities. In addition, the taklim assembly is also a forum for women to develop their potential and actively participate in the social life of the community. There are seven taklim assemblies in Villa Karawangi Housing that routinely hold lectures, trainings, and various empowerment programs involving women from various backgrounds. Therefore, the taklim assembly can be seen as having an important role as a means of women's empowerment based on Islamic values. Keywords: taklim assembly, women's empowerment, religious education.